Ultrasound functional evaluation of fetuses with myelomeningocele: study of the interpretation of results. (2nd October 2017) - Maroto, A.; Illescas, T.; Meléndez, M.; Arévalo, S.; Rodó, C.; Peiró, J. L.; Belfort, M.; Cuxart, A.; Carreras, E.
Abstract: Objective: To assess the reliability of the interpretation of a new technique for the ultrasound evaluation of the level of neurological lesion in fetuses with myelomeningocele. Methods: Observational study including myelomeningocele fetuses, referred to our center for the sonographic assessment of the fetal lower-limb movements, made and recorded by an expert in Maternal–fetal medicine and a specialist in Rehabilitation. Two observers, with different levels of expertise and blinded to each other's results, interpreted each recorded scan two different times. The agreement for the segmental levels assigned between the observers and the gold standard, the inter-observer and intra-observer reproducibility were tested using the weighed Kappa (w κ ) index. Results: Twenty-eight scans were recorded and evaluated. The agreement between the observers and the gold standard remained constant for the expert observer (w κ  = 0.82) and increased (w κ  = 0.66-w κ  = 0.72) for the other one. The inter-observer and the intra-observer variability for the expert observer were w κ  = 0.72 and w κ  = 0.94, respectively. Discussion: The agreement for the prenatal evaluation of the segmental neurological level was excellent, after a short training period, for observers with different degrees of expertise. The interpretation of this technique is reproducible enough and this supports its value for the prediction of postnatal motor function in myelomeningocele fetuses.